Management of resistant biotypes of Eleusine indica and glyphosate-tolerant Spermacocea latifolia with pre-emergent herbicides associated with sequential application of desiccants - Spricigo, Henrique; Schenddelfdt, Bruna Ferrari; Silva, Rafaela Oliva da; Hirata, Andreia Crisitina Silva; Monquero, Patrícia Andrea (Revista de Ciências Agroveterinárias, 2024)
It has been difficult to control Eleusine indica (L.) Gaertn and Spermacocea latifolia Aubl. in cotton and soybean crops due to their herbicide resistance or tolerance to glyphosate. Thus, this study's objective was to evaluate the herbicide efficacy applied in pre-emergence, associated with desiccant herbicide in sequential application, in these species. The experiments for S. latifolia and E. indica were conducted separately in a greenhouse. The experimental design was completely randomized, with 4 replications, in a 6 x 3 factorial. The first factor consisted of pre-emerging herbicides applied two days after the sowing of each species, diclosulam (35 g a.i./ha), s-metolachlor (600 g a.i./ha), pyroxasulfone (200 g a.i./ha) + flumioxazin (200 g a.i./ha), diuron (2000 g a.i./ha), trifluralin (600 g a.i./ha), and the treatment without herbicide. The second factor consisted of the application of diquat (200 g a.i./ha), ammonium glufosinate (400 g a.i./ha), or the absence of sequential application. The results revealed that only for the diclosulam herbicide a sequential application with desiccants was necessary for an effective control of E. indica. The other herbicide applied in pre-emergence showed high efficacy (> 90%) in E. indica control when applied individually. Regarding S. latifolia chemical control, the herbicides s-metolachlor (80.04%), pyroxasulfone + flumioxazin (100%), diclosulam (82.08%) and diuron (89.58%), applied in pre-emergence, presented a satisfactory control at 42 days after emergence. The sequential applications promoted better control of S. latifolia to trifluralin and diuron. In conclusion, there are pre-emergence options for the effective control of E. indica and S. latifolia. However, sequential application can be an important tool for improving the control of some weed species, such as those studied in this work, by certain herbicides.